Molecular species delimitation reveals hidden specific diversity within a freshwater burrowing crayfish (Decapoda: Parastacidae) from southern Chile. Issue 3 (19th April 2021) - Amador, Luis; Victoriano, Pedro F.; D'Elía, Guillermo
Abstract : The Chilean freshwater crayfishes of the family Parastacidae have been little studied, in particular regarding their intraspecific variation. Here we perform an analysis of mitochondrial DNA variation aimed to characterize the genetic diversity and to pose primary hypothesis of species boundaries for populations currently assigned to Parastacus nicoleti, one of the two Chilean currently recognized species. Analyses were based on the mitochondrial gene cytochrome c oxidase subunit I (COI). 206 individuals from 33 localities, along the distributional range of the species, were analysed. We found a deep genealogy that is geographically structured, where most localities present private and closely related haplotypes. Genetic variants fall in nine main divergent and allopatric clades, which form three major clades that latitudinally replace each other. Distinct single locus species delimitation analysis recovers between six and 10 putative species; therefore, we suggest that P. nicoleti is a species complex, which should be further tested with analysis of morphology and nuclear data.